2019
DOI: 10.1002/cam4.2344
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and mutational analyses of colorectal cancer with mutations in the POLE gene

Abstract: Here, we investigated the clinicopathological and mutation profiles of colorectal cancer (CRC) with POLE mutations. Whole‐exome sequencing was performed in 910 surgically resected primary CRCs. Tumors exceeding 500 counts of nonsynonymous single nucleotide variants (SNVs) were classified as hypermutators, whereas the remaining were classified as nonhypermutators. The hypermutators were subdivided into 2 groups. CRCs harboring more than 20% C‐to‐A and less than 3% C‐to‐G transversions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Domingo et al [56] analyzed the frequency of somatic POLE mutations in 6,517 CRCs, and POLE mutations were detected in 1% of CRCs. CRCs with POLE mutations are associated with younger age at diagnosis, male sex, and proximal location [55,56]. Both POLE mutation and MSI-H/MMR-D status were associated with reduced risk of recurrence in a retrospective study [56].…”
Section: Tumor Mutational Burdenmentioning
confidence: 92%
See 1 more Smart Citation
“…Domingo et al [56] analyzed the frequency of somatic POLE mutations in 6,517 CRCs, and POLE mutations were detected in 1% of CRCs. CRCs with POLE mutations are associated with younger age at diagnosis, male sex, and proximal location [55,56]. Both POLE mutation and MSI-H/MMR-D status were associated with reduced risk of recurrence in a retrospective study [56].…”
Section: Tumor Mutational Burdenmentioning
confidence: 92%
“…Three-quarters of TMB-H CRCs are MSI-H, and the remaining one-quarter are MSS with somatic mutations in proofreading genes, mainly polymerase ε (POLE) and polymerase δ (POLD) [53]. In mutation analysis, MSI-H tumors show an insertiondeletion (indel)-predominant pattern, while POLE mutants show a single nucleotide variation-predominant pattern [54,55]. Domingo et al [56] analyzed the frequency of somatic POLE mutations in 6,517 CRCs, and POLE mutations were detected in 1% of CRCs.…”
Section: Tumor Mutational Burdenmentioning
confidence: 99%
“…We extracted the data from these two articles, as presented in Table 2. Data from the Japanese research, 10 which included 910 CRC patients, only included patients from Japan; the article from the Lancet pooling data from clinical trials included 6277 non-Asian CRC patients. 11 We can conclude from the pooled the data that patients with POLE driver mutations are younger than 55 years old and are diagnosed at earlier stages (Japanese research vs. Lancet pooling research: 80.00% vs. 69.70%).…”
Section: Patients Collected From Published Articlesmentioning
confidence: 99%
“…Mice embryo studies have shown synthetic lethality of HRR and NHEJ pathways ( 45 , 46 ). Defective variants in POLD1 and POLE , essential genes in the BER pathway, are related to significantly higher mutational burden and malignancy through BER’s correlation to the MMR pathway ( 47 ). Co-mutations in the MMR and HRR pathways may also be related to hypermutated CRC with worse survival, via interruption of DNA binding and replication ( 48 ).…”
Section: Discussionmentioning
confidence: 99%